VARIABILITY OF CHEMICAL COMPOSITION OF NEWBOULDIA LAEVIS AND ZANTHOXYLUM ZANTHOXYLOIDES RELATED TO ENVIRONMENTAL FACTORS - GBAGUIDI, A. (My University, 2018)
N. laevis and Z. zanthoxyloides leaves from departments of Atlantic, Oueme, Couffo and Zou Area of South Benin were screened for the presence of chemical compounds by standard methods and compared. The results revealed the presence of the following compounds: alkaloids, tannins, flavonoids, quinones, and essential oils in the plant samples regardless of the area and the harvest season. Saponins, cardiac glycosides, cyanogenic glycosides were found to be absent in the leaves of Z. zanthoxyloides and N. laevis regardless of the area and the harvest season. The significance of the plants in traditional medicine and the importance of the distribution of the chemical constituents justified the traditional use of these plants for the treatment of tropical diseases. We recommend further research work on these plants leaves for possible use as a source of raw material for industrial and medical science utilization.
Keywords: Chemical Composition; Newbouldia laevis; Zanthoxylum zanthoxyloides; environmental factors; Benin